Local Diagnostic Reference Levels for Pediatric Interventional Cardiology Procedures in Argentina - Patricia Azcurra; Fernando Leyton; Victorio Lucini; Marcelo Rivarola; Luis Trentacoste; Adela Marques; Juan Chiabrando; Ignacio Seropian; Nicolas Mundo; Carlos Ubeda; Carla Agatiello (MDPI AG, 2023)
The aim of this work was to propose a preliminary local diagnostic reference levels (DRL) for pediatric interventional cardiology (PIC) procedures in Argentina, for different ranges of age and weight. This work has been conducted in the framework of the "Optimization of Protection in Pediatric Interventional Radiology in Latin America and the Caribbean" (OPRIPALC) program coordinated by the World Health Organization and the Pan American Health Organization in cooperation with the International Atomic Energy Agency to ensuring that radiation exposures of pediatric patients are the minimum necessary during fluoroscopy-guided interventional procedures. The local DRL values presented in this paper by weight group and age group were 7.1 Gy·cm2 (<5 kg), 10.7 Gy·cm2 (5-15 kg), 18.0 Gy·cm2 (15-30 kg), 15.9 Gy·cm2 (30-50 kg), and 28.2 Gy·cm2 (50-80 kg) and 5.3 Gy·cm2 (<1), 11.2 Gy·cm2 (1 to 5<), 19.6 Gy·cm2 (5 to 10<), and 21.4 Gy·cm2 (10 to 16<), respectively. Our dose results are among the values found in other international studies; however, there is great potential for dose optimization.